Characterization of AFM cantilevers coated with diamond-like carbon - Salvadori, M.C.; Fritz, M.C.; Carraro, C.; Maboudian, R.; Monteiro, O.R.; Brown, I.G.
The resonance frequency of AFM cantilevers depends on the elastic modulus and on the dimensions of the cantilever. As for coated cantilevers, the resonance frequency will be determined not only by the properties of the cantilever, but also by the properties of the coating (elastic modulus and thickness). We have carried out a systematic investigation of cantilevers coated with several thicknesses of the DLC films. Measurements of the resonance frequency of the cantilevers, before and after the DLC coating, were used with a model to determine the elastic modulus of the DLC. The elastic modulus obtained for the DLC, with this model, was E2s616 GPa. The AFM tip radii were also measured after coating and were found to increase with the DLC film thickness.
Keywords: RESONANCE FREQUENCY; AFM CANTILEVERS; ELASTIC MODULUS